Pendampingan Menghafal Al-Qur’an Menggunakan Metode Kauny Quantum Memory Bagi Siswa RA Amanah Plus Kota Padang - Jasmanidar, Ike Wahyuni; Kustati, Martin; Gusmirawati, Gusmirawati (Jurusan Ilmu Pendidikan - Universitas Lampung, 2024)
Memorizing the Al-Qur'an is an activity that is not easy for young children to do. In carrying out this, a method or method is needed that is easy for children and of course fun for young children, so that it can increase interest and motivation in memorizing the Al-Qur'an for young children. The method that is suitable to be applied is the Kauny Quantum Memory method. The Kauny Quantum Memory method is a way to memorize the Al-Qur'an using a picture story model and fun movements. This method is used in Tahfidz learning for RA Amanah Plus students. The aim of this assistance is to improve students' fine motor skills in memorizing the Al-Qur'an in a fun way using the kauny method. Mentoring is directed at seeing the impact of teaching the Kauny Quantum Memory Method on continuing interest in memorizing RA Amanah Plus students. Apart from that, this assistance aims to find out the results of assistance in memorizing the Al-Qur'an using the Kauny method for Raudhatul Athfal students. The mentoring method used is the Participatory Action Research (PAR) Method. The mentoring stages include goal setting, program design, implementation of activities and evaluation of mentoring activities. The results of the mentoring show that PAI educators are able to provide examples of hand movements to memorize short letters in juz 'Amma. In general, students benefit from assistance in memorizing the Al-Qur'an using the Kauny method. The Kauny Quantum Memory method that has been used is limited to assisting short letters in the Koran, so this method is recommended for daily prayers which are RA's needs.